Time-motion and heart-rate characteristics of adolescent female foil fencers - Wylde, M. J.; Yong, L. . (Journal of Human Sport & Exercise, 2015)
The aims of this study was to understand the time-motion and heart-rate characteristics of adolescent female foil fencing, explore the differences between the 5-touch and 15-touch bouts and compare these results with previous analysis of elite female foil fencers. Eight adolescent female foil fencers (age 14.3 ± 1.2 y, stature 157 ± 3.8 cm, body mass 45.9 ± 5.2 kg) were analysed at a youth fencing competition. Each fencer wore a heart-rate monitor throughout the competition and bouts were filmed so time-motion analysis could be carried out. Five movement classifications were used for the time-motion analysis, this were grouped into three categories based on movement intensity: Low, Moderate and High. High-intensity movement accounted for 8.8 ± 4.4 % of total bout time with a mean duration of 0.8 ± 0.2 s. A higher percentage of low-intensity movement was recorded in the 15-touch bouts, with a higher percentage of high-intensity movement recorded in the 5-touch bouts. The mean duration of low-intensity movement was longer in the 15-touch bouts compared to the 5-touch bouts and a higher mean heart-rate was recorded in the 15-touch bouts compared to the 5-touch bouts. The results from this study suggest that adolescent female foil fencers perform a greater percentage of high-intensity movement in 5-touch bouts compared to 15-touch bouts. However, these fencers demonstrate a higher heart-rate in the 15-touch bouts. The practical application of this study is that adolescent female foil fencers must have a strong aerobic base to maintain a lower heart-rate in competition and ensure that fatigue does not become a limiting factor to performance.